2021
DOI: 10.3390/nu13072210
|View full text |Cite
|
Sign up to set email alerts
|

Myoinositol Reduces Inflammation and Oxidative Stress in Human Endothelial Cells Exposed In Vivo to Chronic Hyperglycemia

Abstract: Myo-inositol (Myo) improves insulin resistance, glucose metabolism, and helps gestational diabetes (GDM) management. GDM is associated with a pro-inflammatory state and increased oxidative stress, which are both involved in vascular damage in diabetes. Our aim was to study Myo anti-inflammatory/antioxidant potential effects on an in vitro model of human umbilical vein endothelial cells (HUVECs). To this end, monocyte cell adhesion to HUVECs, adhesion molecule membrane exposure, and oxidative stress levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Myo -inositol significantly reduced the carbonylation of plasma proteins and provided protection of the thiol groups. A similar decrease in ROS generation was reported in an in vitro model of human umbilical vein endothelial cells (HUVEC), however with a x1000-fold higher concentration of myo -inositol [ 4 ]. Moreover, we examined the selected hemostatic parameters of blood plasma and found that myo -inositol neither modified the activated partial thromboplastin time (APTT), the prothrombin time (PT), nor the thrombin time (TT).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Myo -inositol significantly reduced the carbonylation of plasma proteins and provided protection of the thiol groups. A similar decrease in ROS generation was reported in an in vitro model of human umbilical vein endothelial cells (HUVEC), however with a x1000-fold higher concentration of myo -inositol [ 4 ]. Moreover, we examined the selected hemostatic parameters of blood plasma and found that myo -inositol neither modified the activated partial thromboplastin time (APTT), the prothrombin time (PT), nor the thrombin time (TT).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, myo -inositol may also be found in its free form or a derivative form, where it can act upon various processes including stress responses, metabolic homeostasis, the permeability of ion channels and even the regulation of mRNA. Myo -inositol has also been shown to have anti-inflammatory/antioxidant capabilities and is a possible vasodilator [ 3 , 4 ] with a good therapeutic option in the reduction of metabolically induced inflammation [ 5 ]. These properties may provide protection to the vascular system, which is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HUVECs obtained from women with GDM who were treated with myo-inositol throughout the pregnancy had a markedly reduced number of monocytes attached to their surface, less adhesion molecule exposure, and lower intracellular oxidative stress levels in comparison to those of women treated with diet only. The same effects were observed after 48h hours of stimulation with myo-inositol in in vitro conditions [ 183 ]. Another in vitro study revealed that metformin improves cell migration and stimulates angiogenesis of HUVECs.…”
Section: Discussionsupporting
confidence: 65%